Peran Sosial Agensi Dalam Kegiatan Komunitas KamiSketsa Galeri Nasional Indonesia - Nugraha, Daniel (Urban: Jurnal Seni Urban, 2018)
Sketching as an activity that can make a bridge for art audience becoming an artist is a choice of educational activities chosen by National Gallery of Indonesia. KamiSketsa Galnas has successfully launched three sketch exhibitions with integrated and growing achievements. Anthony Giddens’ Structural Theory will be used in this study to reveal the social role of agency. The methods used are (1) the method of observation by examing the arrangement of events from poster and sketch work, and (2) the method of interviewing the team and participant of KamiSketsa Galnas. The results of this study reveals the success of the sketch work which show significants developments both in terms of technique and narrative, and the results of the interview focus on Zamrud Setya Negara as Head of Exhibition and Partnership of the National Gallery of Indonesia who acts as both a planner and as a sketcher so that he can “naturally” grow the sketch community KamiSketsa Galnas. This research reveals that Giddens’ thought explains that some of the Agency’s social actions are able to reorganize a new system and order in art while remaining within the structure. The streght of the practical continuity, which routinely crosses time and space, has shown positive results through the development of KamiSketsa Galnas.Sketsa merupakan salah satu kegiatan yang dapat menjembatani seseorang menjadi penikmat sekaligus bisa menjadi pelaku seni. Melalui KamiSkesa, Galeri Nasional Indonesia bertekad untuk memberikan wadah dan edukasi bagi para pelaku dan penikmat seni. Penelitian ini akan membahas peran Galeri Nasional sebagai sosial agensi dalam kegiatan KamiSketsa yang digagas oleh Galeri Nasional. Teori Strukturasi dari Anthony Giddens akan digunakan dalam penelitian ini untuk mengungkap peran sosial agensi. Metode yang digunakan adalah (1) metode observasi dengan meneliti susunan acara melalui penanda poster dan karya serta (2) metode wawancara kepada tim penyelenggara dan peserta KamiSketsa Galnas. Hasil penelitian ini mengungkap keberhasilan karya sketsa yang menunjukkan perkembangan signifikan baik dari segi teknik maupun narasinya. Penelitian ini juga mengungkap bahwa soaial agensi yang digagas Giddens mampu menata kembali sebuah sistem dan tatanan baru dalam seni dengan tetap berada di dalam struktur. Kekuatan kontuinitas praksis yang rutin melintasi ruang dan waktu telah menunjukkan hasil positif melalui perkembangan KamiSketsa Galnas.